EVALUASI PEMBERDAYAAN PROGRAM BANTUAN SOSIAL DARI PEMERINTAH REPUBLIK INDONESIA PADA MASA PANDEMI COVID-19 - Era Purike (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2021)
The COVID-19 pandemic has an impact on public health and affects the economic conditions, education, and social life of the Indonesian people. The decline in these activities impacts the socio-economic conditions of the community, especially the vulnerable and poor. The COVID-19 pandemic has led to an increasingly diverse group of vulnerable groups with complex conditions in layers. In response, the government carried out several policies by providing some social assistance to the community. Social assistance from the government is distributed to the community through a mechanism for distributing aid that existed long before the pandemic. This study is intended to obtain an overview of the social assistance provided by the government of the Republic of Indonesia during the COVID-19 pandemic, whether it has been able to empower beneficiaries or not. This study uses a literature review and a limited survey. In evaluating empowerment, the researcher was guided by the theory of empowerment, self-determination, the use of processes, and the theory of use and action. The researcher concludes that the government's social assistance program to both individuals and MSMEs has not been able to empower the beneficiaries. However, some reasons for those conclusions are several factors. The most reason is the data on beneficiaries that have not been updated and the assistance that is not well-targeted. On the other hand, the assistance failed to improve the skills of the beneficiaries. The absence of evaluation and the confusion of the stakeholders responsible for this social assistance program lead the program to be more complicated.